What is clearance worth? Patients' stated risk tolerance for psoriasis treatments. (17th November 2017) - Fairchild, Angelyn O.; Reed, Shelby D.; Johnson, F. Reed; Anglin, Greg; Wolka, Anne M.; Noel, Rebecca A.
Abstract: Purpose: The purpose of this study was to provide quantitative evidence of patients' tolerance for therapeutic risks associated with psoriasis treatments that could offer psoriasis improvements beyond the PASI 75 benchmark. Materials and methods: We used a discrete-choice experiment in which respondents chose between competing psoriasis treatments characterized by benefits (i.e. reduced plaque severity, reduced plaque area), risks (i.e. 10-year risk of tuberculosis, 10-year risk of death from infection), and treatment regimen. We analyzed choice data using random-parameters logit models for psoriasis affecting the body, face, or hands. Results: Of 927 eligible members of the National Psoriasis Foundation who completed the survey, 28% were unwilling to accept any greater risk of treatment-related infection mortality. Among the remaining 72%, respondents were willing to accept higher risks of infection-related mortality associated with treatment to completely remove plaques covering only 1% of the body, compared to reducing lesions from 10 to 1% of the affected area. This finding was more pronounced for lesions on the face. Conclusions: Most patients placed greater value on eliminating even very small plaques compared to avoiding treatment-related risks. The perceived importance of complete versus near-complete clearance was stronger than previously documented.